The Analysis of Translation Technique of Children Story : “Lila, the Clumsy Witch” - Maisa, Maisa (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2014)
Regarding to Douglas Robinson, in his famous book entitled Becoming atranslator, 1998; 49, define translation is an intelligent activity involving complex processes of conscious and unconscious learning.In the other book of Peter Newmark's, a textbook of translation, stated that translation is rendering the meaning of a text into another language in the way that the author intended the text. Newmark describe translation techniques into two catagories. First, translation which focuses on the source language and target language. The SL translation techniques consists of four such as word fo word, literal, faithfull and semantic translation. While the techniques which focuses on Target Language (TL). The techniques are adaptation, free translation, idiomatic translation and  communicative translation.In this paper, the writer would like to analyze the children text entitled Lila, the clumsy witch or Lila, penyihir yang ceroboh. “ what kind of translation techniques does the writer use in translating the text ? The story is written by Amelia Kurniawati and translated by P. Francis Rhien. The result is that the writer of the book uses more techniques of translation which focuses on Source language using word for word translation 19,3%, Literal translation 61,5% and Free translation 19,3%. This result indicates that the writer of the book focuses on the source language.